Stakeholder Trust In the Use of E-Voting: Organizing The Election of Simultaneous Village Heads In Sleman Regency 2020 - Rahmanto, Fajar; Nurmandi, Achmad; Kusuma Dewi, Dian Suluh; Salahudin, Salahudin (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
One of the technological developments in politics is the use of E-Voting technology in elections. E-Voting has been done to improve the quality of election results and reduce votes after the election. This paper discusses explaining the purpose of E-Voting in holding simultaneous village head elections in Sleman Regency using descriptive qualitative methods. This type of data consists of content from websites, local government, and online news with analysis using the Nvivo 12 Software plus the explore crosstab query and cluster analysis. This paper reveals that the level of trust in the use of technology in E-Voting from the Regional Government of Sleman Regency of 29.23% will affect the effectiveness of 32.31%, efficiency 21.54%, and transparency the election results of 10.77%. To realizing agreement and energy in the election of village heads based on E-Voting in Sleman Regency, a ballot replacement will carry out with a "smart card." The readiness of human resources from the organizers was carried out with workshops and technical guidance against the primary professional staff (TTU) and field technical staff (TTL). To support the community's readiness, the Regional Government conducts socialization and simulation in advance about the use of E-Voting tools.